2018
DOI: 10.1123/apaq.2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Career Development and Learning Pathways of Paralympic Coaches With a Disability

Abstract: The purpose of this study was to gain an understanding of the career development and learning pathways of Paralympic head coaches who previously competed as Paralympic athletes. Each coach participated in a semistructured interview. A thematic analysis of the data revealed three higher order themes, which were called becoming a coach, learning to coach, and lifelong learning and teaching. Across these themes, participants discussed interactions with other coaches and athletes with a disability, learning from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
0
9
1
7
Order By: Relevance
“…Ressaltamos que conhecimentos específicos a respeito das deficiências são necessários para efetividade no trabalho (CÔTÉ; GILBERT, 2009) e desenvolvimento do conhecimento profissional do treinador (CREGAN;REID, 2007;MCMASTER;WERTHNER, 2012;TAWSE et al, 2012). Por outro lado, estudos reportam que a trajetória do treinador não se limita à situações formais, pois os cursos de graduação não aprofundam a abordagem de questões sobre atletas com deficiência e suas particularidades no treinamento (DUARTE;FAIRHURST;HARVEY, 2017;WAREHAM et al, 2017;DOUGLAS;. Para tanto, a aprendizagem ocorre durante toda a vida e até mesmo antes de iniciar o curso superior (DUARTE;MILISTETD et al, 2015).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Ressaltamos que conhecimentos específicos a respeito das deficiências são necessários para efetividade no trabalho (CÔTÉ; GILBERT, 2009) e desenvolvimento do conhecimento profissional do treinador (CREGAN;REID, 2007;MCMASTER;WERTHNER, 2012;TAWSE et al, 2012). Por outro lado, estudos reportam que a trajetória do treinador não se limita à situações formais, pois os cursos de graduação não aprofundam a abordagem de questões sobre atletas com deficiência e suas particularidades no treinamento (DUARTE;FAIRHURST;HARVEY, 2017;WAREHAM et al, 2017;DOUGLAS;. Para tanto, a aprendizagem ocorre durante toda a vida e até mesmo antes de iniciar o curso superior (DUARTE;MILISTETD et al, 2015).…”
Section: Discussionunclassified
“…A organização e planejamento do treinamento é uma das principais funções do treinador (CÔTÉ et al, 1995), e o domínio desse conhecimento é essencial para sua efetividade (CÔTÉ; GILBERT, 2009). Assim, é necessário que programas de capacitação se estruturem para oferecer oportunidades de estágios aos treinadores aspirantes no desenvolvimento de suas habilidades e carreira profissional (FAIRHURST;HARVEY, 2017;WAREHAM et al, 2017;DOUGLAS;.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Lack of coach development and education programs lead to coaches relying on experiential knowledge and informal communication with colleagues as means of coach development (Dehghansai et al, 2019), even reaching out to coaches from different sports (Duarte et al, 2018). In addition, recent evidence has found that Para sport coaches tend to progress through the coaching ranks to national coaching positions relatively quickly and may not be fully equipped with the necessary experience, knowledge, or resources to support their transition (McMaster et al, 2012;Douglas et al, 2018). Therefore, new coaches could benefit from networking with other coaches in Para sport (including attending conferences, workshops, etc.…”
Section: Interpersonal Environmental Constraintsmentioning
confidence: 99%